PERENCANAAN JADWAL PERAWATAN DAN MENCARI PENYEBAB KEGAGALAN POMPA SUBMERSIBLE DENGAN METODE FTA DAN RCM - Alfariz, Rafi; Sumarta, Dewi Mulyasari; Setiawati, Tini (Universitas Majalengka, 2025)
PT Batra Alam Sejahtera is a company engaged in water drilling services and clean water management. The clean water distribution system carried out by the company is to collect water flowed from several boreholes by submersible pumps to the storage tank, so that damage to one of the submersible pumps will affect the amount of water supply produced and have an impact on the water discharge that can be flowed to consumers. Submersible pump well 2 has the highest downtime among the 3 submersible pumps used, the engine performance should be maintained to ensure all consumers can be supplied with clean water, so an analysis of pump maintenance is needed so that pump performance can be maintained. To overcome this problem, this research aims to find the cause of damage to the pump with the Fault Tree Analysis method and determine the maintenance schedule time with the Reliability Centered Maintenance method. The initial step is to find the cause of the damage by creating a fault tree structure, followed by the calculation of TTR, TTF, MTTR, MTTF, Reliability and maintenance time intervals so that the final goal of the research is to create a maintenance schedule for both submersible pump components, namely Electromotor and Impeller. Based on the results of the fault tree structure analysis, the causes of submersible pump damage can be caused by the use of inappropriate electromotor, impeller, and cable specifications, damaged bearings, interference from the electricity network used, no protection system, inappropriate automatic radar settings, damaged electromotor seals, no regular maintenance schedule, workers lack of understanding and lack of thoroughness when installing. Based on the results of this study with a reliability value of 80%, the inspection interval time for the Electromotor component is 1002.2 hours and the Impeller component is 1637.7 hours with maintenance actions taken, namely inspection, cleaning, and component replacement.